2019
DOI: 10.1097/fch.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences, Duration of Stay in the United States, and Serious Psychological Distress

Abstract: Using data from the 2002-2012 National Health Interview Surveys, this study examines the association between duration of stay in the United States and serious psychological distress (SPD) among Middle Eastern (ME) immigrants and tests whether this association differs by sex. Results show that although ME immigrant women with longer duration are significantly more likely to report SPD than US-born white women, the SPD of ME immigrant men do not significantly differ from that of US-born white men. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Two studies reported a prevalence of SPD (8.33%). SPD refers to mental health problems that cause moderate to severe impairment in social or occupational functioning (Alkaid Albqoor et al, 2020; Shafeek Amin & Driver, 2019). Both studies reported a similar rate (5.10% and 6.72%) of SPD among Middle Eastern immigrants (Alkaid Albqoor et al, 2020; Shafeek Amin & Driver, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported a prevalence of SPD (8.33%). SPD refers to mental health problems that cause moderate to severe impairment in social or occupational functioning (Alkaid Albqoor et al, 2020; Shafeek Amin & Driver, 2019). Both studies reported a similar rate (5.10% and 6.72%) of SPD among Middle Eastern immigrants (Alkaid Albqoor et al, 2020; Shafeek Amin & Driver, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies (54.16%) examined mental health in general or multiple mental health conditions in the same study. Some studies specifically focus on specific mental health conditions such as depression (33.33%, n = 8; Arfken et al, 2018; Jamil et al, 2007; Javanbakht et al, 2019; Kamimura et al, 2018; Kroll et al, 2011; M'zah et al, 2019; Piwowarczyk et al, 2014; Taylor et al, 2014), anxiety (16.66%, n = 4; Javanbakht et al, 2019; M'zah et al, 2019; Piwowarczyk et al, 2014; Taylor et al, 2014); posttraumatic stress disorder (PTSD; 29.16%, n = 7; Arfken et al, 2018; Jamil et al, 2007; Javanbakht et al, 2019; Kulwicki & Ballout, 2015; M'zah et al, 2019; Norris & Aroian, 2008; Taylor et al, 2014); psychoses (4.16%, n = 1; Kroll et al, 2011); perinatal mental disorder (12.50%, n = 3; Alhasanat et al, 2017; Alhasanat‐Khalil et al, 2018, 2019); severe psychological disorders (8.33%, n = 2; Alkaid Albqoor et al, 2020; Shafeek Amin & Driver, 2019), and suicide (4.16%, n = 1; El‐Sayed et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations